Novel synthesis of RGO/NiCoAl–LDH nanosheets on nickel foam for supercapacitors with high capacitance. Issue 114 (1st December 2016) - Su, Weifang; Lin, Tao; Chu, Wei; Zhu, Yachao; Li, Jing; Zhao, Xiusong
Abstract : Hierarchically flower-like RGO/NiCoAl–LDH@NF hybrid has been fabricated by a facile, green approach, giving a high electrochemistry performance with high and stable specific capacitance. Abstract : A novel nano-flower RGO/NiCoAl–LDH composite was fabricated through a smart binder-free hydrothermal process, for advanced electrochemical energy storage in supercapacitors. The morphology of the nano-flower structure was self-assembled using several nanosheets vertically interconnected with each flake, and the as-obtained nano-flower structure of the porous nanosheet morphology greatly enhanced the capacitance and the rate capacity of the electrode material for supercapacitors. When the composite was used in an electrode, the sample with 6.36 mg graphene oxide revealed surprising and optimized high performance. There was ultrahigh specific capacitance of 4732 F g −1 at 1 A g −1, and 4068 F g −1 at 4 A g −1, showing a good performance. The results exhibited the synergy and advantages of RGO with NiCoAl–LDH on a nickel foam carrier with nano-flower morphology. The results exhibit the superiority of the modified active metal substrate and elaborate graphene's influence on the material morphology. This will open up broad prospects for the future field of electrode materials for supercapacitors.